2004
DOI: 10.1038/nm1003
|View full text |Cite|
|
Sign up to set email alerts
|

VX-680, a potent and selective small-molecule inhibitor of the Aurora kinases, suppresses tumor growth in vivo

Abstract: The Aurora kinases are essential for the regulation of chromosome segregation and cytokinesis during mitosis. Aberrant expression and activity of these kinases occur in a wide range of human tumors, and lead to aneuploidy and tumorigenesis. Here we report the discovery of a highly potent and selective small-molecule inhibitor of Aurora kinases, VX-680, that blocks cell-cycle progression and induces apoptosis in a diverse range of human tumor types. This compound causes profound inhibition of tumor growth in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
848
4
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 902 publications
(904 citation statements)
references
References 42 publications
49
848
4
3
Order By: Relevance
“…The Aurora kinases represent one such class of molecular targets that are essential for progression through mitosis, and small molecule inhibitors of these kinases possess broad antitumor efficacy that has not yet been shown to discriminate on a cancer genetic basis. 7,11 Although it has been demonstrated that cancer cells deficient in p53 show accelerated polyploidization when treated with VX-680, 23 this does not appear to represent genetic susceptibility per se as cells harboring wild-type p53 are also subject to polyploidization-mediated cell death, though perhaps with delayed kinetics. Our data provide genetic evidence to indicate that the Aurora kinase inhibitor, AZD1152, which is currently undergoing clinical evaluation and potentially of another clinical compound, VX-680, may be relatively ineffective in tumor cells that overexpress MDR1 or BCRP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Aurora kinases represent one such class of molecular targets that are essential for progression through mitosis, and small molecule inhibitors of these kinases possess broad antitumor efficacy that has not yet been shown to discriminate on a cancer genetic basis. 7,11 Although it has been demonstrated that cancer cells deficient in p53 show accelerated polyploidization when treated with VX-680, 23 this does not appear to represent genetic susceptibility per se as cells harboring wild-type p53 are also subject to polyploidization-mediated cell death, though perhaps with delayed kinetics. Our data provide genetic evidence to indicate that the Aurora kinase inhibitor, AZD1152, which is currently undergoing clinical evaluation and potentially of another clinical compound, VX-680, may be relatively ineffective in tumor cells that overexpress MDR1 or BCRP.…”
Section: Discussionmentioning
confidence: 99%
“…ethyl Dihydrogen Phosphate) 10 and VX-680/MK-0457 (cyclopropane carboxylic acid {4-[4-(4-methyl-piperazin-1-yl)-6-(5-methyl-2H-pyrazol-3-ylamino)-pyrimidin-2-ylsulphanyl]-phenyl}-amide) 38 have been disclosed. These compounds were synthesized at Abbott Laboratories for comparative purposes.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aurora kinases are known to have a central role in the control of mitosis (Barr and Gergely, 2007). The pan-aurora kinase inhibitor VX-680 was used for these experiments (Harrington et al, 2004). VX-680 on its own caused an increase in the number of senescent MCF7 cells and also enhanced the effects of PKCi depletion on senescence induction (Figure 6a).…”
Section: Pik3ca Mutations Increase the Expression And Activation Of Pkcimentioning
confidence: 99%
“…Biomarkers identified for AK-A and AK-B are phosphorylated Aurora kinase A and phosphorylated histone H3, respectively [23,24,25]. We will make use of these relationships.…”
Section: Spindle Checkpoint Modelmentioning
confidence: 99%